SIKAP PENONTON DALAM PROGRAM TELEVISI INDONESIA SAAT INI - Rahmat Edi Irawan (Jurnal Sosiologi Reflektif, 2015)
The study in this paper is motivated increasing reports or complaints against television delivered to the Indonesian Broadcasting Commission (KPI). This paper aims to look at how the shift from a passive audience or spectators into active audience or spectators give feedback on television shows that they receive, which is now starting to look also at the television audience in Indonesia. Methodology or study in this paper uses literature, to see how the exercise of some theories of mass communication, particularly with regard to the impact of television on the audience. Conclusions or the results of the study for this paper is to begin the shift to a passive audience active audience in the television industry in Indonesia today. If in the past, many obstacles, such as a repressive regime, not the choice of programs and television stations as well as the lack of regulation and the regulator has ever television audience in Indonesia passive. While today, empowering the audience various media and efforts made KPI caused his condition has changed, the audience began to be active. It was indicated by increasing their critical stance, with the umber of impressions made complaints on violation of regulations either through KPIs or other mass media.